2013
DOI: 10.1074/jbc.m112.424358
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-rich Protein 61 (CCN1) Domain-specific Stimulation of Matrix Metalloproteinase-1 Expression through αVβ3 Integrin in Human Skin Fibroblasts

Abstract: Background: Elevated MMP-1 is a prominent feature of human skin aging. Results: The CCN1 VWC domain interacts with ␣V␤3 integrin and cooperates with adjacent IGFBP and TSP1 domains to stimulate MMP-1 expression. Conclusion: CCN1 structural domains contribute to human skin aging. Significance: Targeting the CCN1/␣V␤3 integrin pathway may provide a therapeutic approach to improve the health of aged human skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…In cultured human dermal fibroblasts, the elevated expression of CCN1 not only inhibits the expression of type I procollagen, but also concurrently increases the expression of multiple MMPs and cytokines [36,38,39,77].…”
Section: Ccn1 Functions As a Critical Mediator Of Oxidative Stress-inmentioning
confidence: 99%
See 1 more Smart Citation
“…In cultured human dermal fibroblasts, the elevated expression of CCN1 not only inhibits the expression of type I procollagen, but also concurrently increases the expression of multiple MMPs and cytokines [36,38,39,77].…”
Section: Ccn1 Functions As a Critical Mediator Of Oxidative Stress-inmentioning
confidence: 99%
“…As described below, oxidative stress can result in the following: inducing multiple matrix metalloproteinases (MMPs), which cause fragmentation of collagen fibrils [7,20,[36][37][38][39][40]; inhibiting TGF-β signaling, which causes inhibition of the collagenous ECM production [1,39,41]; and inducing multiple age-related pro-inflammatory cytokines, which create an inflammatory dermal microenvironment (inflammaging) [35,39,42]. These ROS-induced alterations of the dermal ECM microenvironment are the driving force for the most prominent clinical features of aged skin, including thinning and increased fragility of the skin [5,7,8,20,[43][44][45].…”
Section: Collagen Fragmentation Collapses Dermal Fibroblasts and Incrmentioning
confidence: 99%
“…1F). CCN1 protein is composed of five distinct domains, and the domain-specific function plays essential roles in the pathogenesis of multiple human diseases (15,39). To determine whether a specific domain of CCN1 protein mediated its exosome-shuttled secretion after CSE, five CCN1 constructs were generated in which one of the specific domains was deleted (Fig.…”
Section: Cs Augmented Ccn1 Secretion and Induced Ccn1 Cleavage In Lunmentioning
confidence: 99%
“…In this study, we mapped the CCN1 epitope for 093G9, which is located in the IGFBP domain of CCN1. Consistently, it has been shown that the IGFBP domain of CCN1 is required for CCN1 to stimulate MMP1 expression . However, little is known about the molecular mechanisms underlying the multifaceted CCN1 functions yet.…”
Section: Discussionmentioning
confidence: 84%